Soft facial profile and distal relation of second molars in children with complete primary dentition - Maldonado Araya, Felipe (2019)
Objetive. To observe the types of soft facial profile according to the angles of facial convexity (FCA) and total facial convexity (TFCA), in addition to evaluating their relationship with the distal position of the primary second molars in children between 3 and 5 years. Methods. Twenty-eight out of 200 children with complete primary dentition were examined to determine the distal relation of primary second molars, and a digital photographic examination of their lateral profile was performed to evaluate the ACF and ACFT. With the Fisher's exact test, soft tissue profiles were compared according to age and gender, and with Student t test for a single sample, the angular averages were evaluated. Results. The mean of the FCA was 167.1 ° ± 5.1, and the TFCA was 145.8 ° ± 3.7. A high convexity of the FCA was observed in 21.4% of the children, medium in 60.7% and low in 17.9%. While in the TFCA it was divided into 17.9% with high convexity, 67.9% medium and 14.2% low. The average value of the FCA for the mesial step, flush terminal and distal step 169.2 ° ± 3.7, 168 ° ± 4.9 and 162.5 ° ± 4.8, while the average of the TFCA was 146.7 ° ± 4.4, 146.3 ° ± 3.6 and 143.5 ° ± 2.8 respectively. Conclusions. A significant relationship between the presence of a high convex profile and a distal step molar relationship was observed for the FCA, as well as a significant difference between the average of this angle in distal step compared to the reference average.